PENGARUH FASILITAS, PELAYANAN, PRODUK DAN HARGA TERHADAP KEPUASAN TAMU DI RESTORAN EDEN DAILY INTERNATIONAL FOOD SEMARANG - Ahmad Mansur; Ayuk Kurniyawati (Jurnal Akuntansi dan Pajak, 2023)
This research conducted in Eden Daily International Food Semarang, to determine the affect of product, price, quality service, and guest satisfaction. Research data was obtained through questionnaires and the sample used in this research is 87 respondents. The result of the study are expected to provide useful information for the manager and guest satisfaction.The data obtained were processed by using descriptive analysis and quantitative statistical analysis.Quantitative analysis uses multiple regression analysis to determine the effect of independent variables to dependent variable,model test,hypothesis test,and yet before the test is done first test the validity and reliability test. The result of regression analysis indicates that increasing product, price, and quality service will be followed increasing guest satisfaction, as well as on the contrary. The result of regression analysis test indicated that value of F is significant, with correlation value determination adjusted R2 as big as 0,855. This case inform that guest satisfaction influenced by product, price, and quality servicewith percentage 85,5%. This case indicates that to increasing guest satisfaction, need to increase product, price, and quality service as well. Keyords : Product, Price, Quality Service and Guest Satisfact